The implications of an invasive species on the reliability of macroinvertebrate biomonitoring tools used in freshwater ecological assessments. (April 2016) - Mathers, Kate L.; Chadd, Richard P.; Extence, Chris A.; Rice, Stephen P.; Wood, Paul J.
Highlights: Effects of invasive crayfish on macroinvertebrate biomonitoring tools are examined. Abundance weighted indices were statistically inflated after invasion. Biomonitoring tools based on presence of occurrence were not affected. Inflation of scores was greatest during the autumn routine monitoring period. Abstract: Invasive species represent one of greatest threats to aquatic biodiversity globally and are widely acknowledged to be instrumental in modifying native community structure. Despite this, little is known about how the increasing range expansion of invasive taxa may affect routine biomonitoring tools widely employed to measure or quantify environmental quality in lotic systems. This study examined the impact of an invasive freshwater crayfish on commonly employed riverine macroinvertebrate biomonitoring tools (scores and indices) designed to respond to a range of stressors. Data from long-term monitoring sites on both 'control' and invaded rivers in England were examined to assess changes to biomonitoring scores following invasion by signal crayfish ( Pacifastacus leniusculus ). Results indicate that routine biomonitoring tools used to quantify potential ecological stressors which are weighted by abundance, such as the Lotic-invertebrate Index for Flow Evaluation (LIFE) score and Proportion of Sediment-sensitive Invertebrates (PSI), were subject to significant inflation following invasion. In contrast, indices based simply on the presence of taxa, such as the Average Score Per-Taxon (ASPT – a derivative of BMWP), displayed no changes compared to control rivers; or in the case of the Biological Monitoring Working Party Score (BMWP), NTAXA and EPT richness, no consistent pattern following invasion. Season had a significant effect on the interaction of crayfish and LIFE and PSI scores. Autumn samples were subject to statistical inflation following crayfish invasion whilst spring samples exhibited no significant change. The results suggest that care should be taken when interpreting routine macroinvertebrate biomonitoring data where non-native crayfish are present, or in instances where their presence is suspected.